Comparison of hierarchical and six degrees-of-freedom marker sets in analyzing gait kinematics. Issue 2 (25th January 2016) - Schmitz, Anne; Buczek, Frank L.; Bruening, Dustin; Rainbow, Michael J.; Cooney, Kevin; Thelen, Darryl
Abstract : The objective of this study was to determine how marker spacing, noise, and joint translations affect joint angle calculations using both a hierarchical and a six degrees-of-freedom (6DoF) marker set. A simple two-segment model demonstrates that a hierarchical marker set produces biased joint rotation estimates when sagittal joint translations occur whereas a 6DoF marker set mitigates these bias errors with precision improving with increased marker spacing. These effects were evident in gait simulations where the 6DoF marker set was shown to be more accurate at tracking axial rotation angles at the hip, knee, and ankle.